A study on English vocabulary learning strategies exploited by the second-year students of different learning style preferences at School of Law, VNU = Nghiên cứu các phương pháp học từ vựng tiếng Anh của sinh viên năm hai thuộc các nhóm phong cách học kh - Nguyễn, Thị Huyền Trang (University of Languages and International Studies, 2017)
67 tr. + CD-ROM + tóm tắt